The Right to Education as a Basic Right in the Context of Law and Pancasila - Lestari, Dwi Apriliani Indah (Indonesian Journal of Pancasila and Global Constitutionalism, 2022)
In this era of globalization where the times are increasingly modern and increasingly advanced, especially in Indonesia, which respects human rights very much, to be able to equalize the right to education in Indonesia is not easy because the territory of Indonesia is very wide and has many differences. Technology in various regions also plays an important role in progress in equitable distribution of education considering that in eastern Indonesia technological progress itself is not evenly felt throughout the community. it is the duty of the government to overcome this challenge for the future of the Indonesian nation and to realize Indonesia's goal of educating the nation's life. Not only because of the region, the difference in social status in society can also affect the distribution of education in Indonesia. In writing this article, it is hoped that it will be a correction for all Indonesian people to always uphold the right to education for all levels of Indonesian society indiscriminately in order to realize it in the ideals of the Indonesian nation as expected by the ancestors.